Formal rules and its role in centralised-diffusion systems: A study of small-scale producers of oil palm in Colombia. (April 2021) - Bernal-Hernández, Paloma; Ramirez, Matias; Mosquera-Montoya, Mauricio
Abstract: This paper explores the different pathways of technology diffusion and the resulting impacts on technology adoption that can emerge following a strategy to incorporate vulnerable communities of small-scale producers into traditionally top-down governance agribusiness systems. Building on the Contract Farming Arrangements (CFA) literature, we suggest that despite high levels of top-down control and the mono systems of diffusion that these practices imply, diffusion forms can vary considerably according to the motivations that drive different types of producers and the variances in local governance. We summarise these diffusion forms as a diffusion pathway of governance dictated by dominant change agent control and a diffusion pathway of governance dictated by change agent control and user participation. An important contribution of the paper is to highlight the critical role of formal rules in defining the types of governance for the creation of these different pathways. However, additional factors associated with the participation of smallholders such as attachment to land, engagement in collective action and long-term sustainability visions also introduce variations in these pathways and define the results of technology adoption. The study focuses on the Colombian oil palm sector; a key agribusiness sector targeted by policy makers with a strategy to integrate small-scale farmers into the agribusiness value chain as a means to relieve poverty and reduce levels of rural violence associated with conflicts over land and production of elicit crops. Highlights: Formal rules are a critical factor in the theory of innovation diffusion. Different diffusion forms can emerge within centralised-diffusion systems. Technology adoption can vary due to degree of attachment to agricultural production and long/short term vision. Technology adoption can vary due to engagement in collective action and motivation of agents. Values of trust embedded in agreements and technical relationships can impact the adoption of short-term practices.